STUDI ANALISIS PERAN KEMENTERIAN AGAMA DALAM PENGELOLAAN ZAKAT PROFESI ASN DI KOTA BATU - Khozainul Fauziah; Ibnu Jazari; Syamsu Madyan (Jurnal Hikmatina, 2021)
This article discuss the analysis studies of the role of the ministry religion in the management of professional zakat which focuses in the ministry religion in Batu. There are two focus in this article, namely; 1. What is the role of the ministry religion in Batu in the management of professional zakat; 2. How is the system of management professional zakat for ASN in Batu. This research applies two types of research, namely, library research and analytical studies.